2006
DOI: 10.1002/ajp.20337
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variation within and among regional populations of longtail macaques (Macaca fascicularis) in relation to other species of the fascicularis group of macaques

Abstract: An 835 base pair (bp) fragment of mitochondrial DNA (mtDNA) was sequenced to characterize genetic variation within and among 1,053 samples comprising five regional populations each of longtail macaques (Macaca fascicularis) and rhesus macaques (Macaca mulatta), and one sample each of Japanese (M. fuscata) and Taiwanese (M. cyclopis) macaques. The mtDNA haplotypes of longtail macaques clustered in two large highly structured clades (Fas1 and Fas2) of a neighbor-joining tree that were reciprocally monophyletic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
138
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(166 citation statements)
references
References 43 publications
26
138
2
Order By: Relevance
“…These tendencies are consistent with previous reports of mtDNA diversity [5,35], microsatel- [5,35], microsatel-, microsatellite polymorphisms [3], and major histocompatibility complex genes [1, 16, 2�]. However, genetic comparison among the three subpopulations revealed intermingled phylogenetic relationships (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These tendencies are consistent with previous reports of mtDNA diversity [5,35], microsatel- [5,35], microsatel-, microsatellite polymorphisms [3], and major histocompatibility complex genes [1, 16, 2�]. However, genetic comparison among the three subpopulations revealed intermingled phylogenetic relationships (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…As an important genetic marker, maternally-inherited mitochondrial DNA (mtDNA) warrants special attention for genetic investigations such as intraspecies variation [35], population structure [10,12,13,20,34], phylo-, population structure [10,12,13,20,34], phylo- [10,12,13,20,34], phylo-, phylogeography [5,23,26,37], and demography [24] in ma- [5,23,26,37], and demography [24] in ma-, and demography [24] in ma- [24] in main macaque species. In particular, the mtDNA control (D-loop) region is composed of �00 to 1,000 base pairs (bp) and contains hypervariable segments 1 (HVI) and 2 (HVII).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In all populations, the X/A diversity ratios were much lower than those reported for other primates including humans (e.g., Pool and Nielsen 2007;Hammer et al 2008;Keinan et al 2009;Hvilsom et al 2012). In addition, Philippine macaques, which are thought to have originated by migration from continental populations (e.g., Smith et al 2007), showed lower X/A diversity ratio than Indonesian-Malaysian macaques. The difference between the Indonesian-Malaysian and Philippine populations was statistically significant (P = 0.002; permutation test).…”
Section: Resultscontrasting
confidence: 57%